How are adults with intellectual and/or developmental disabilities represented, included and engaged in cancer research: A scoping review protocol - Rebecca L. W. Hansford; Sandra Halliday; Nicole Bobbette; Laura Mullins; Christina Godfrey; Anna Przednowek; Preeyaporn Srasuebkul; Martin McMahon; Alyson L. Mahar (PLoS ONE, 2026)
Cancer research has shifted to highlight and empower the voices and experiences of patients in informing and guiding research. Adults with intellectual and/or developmental disabilities experience worse cancer-related outcomes compared to those without disabilities, including lower screening rates, more advanced stages at diagnosis, and lower survival likelihood. However, limited research has been conducted on how they are involved in cancer research. To improve how cancer-related care is provided to adults with intellectual and/or developmental disabilities, it is imperative that they are included in research that affects them. The objective of this scoping review is to explore and synthesize how adults with intellectual and/or developmental disabilities are represented, involved, and engaged in cancer research. This study will follow the JBI methodology for scoping reviews. Embase, Medline, PsycINFO and CINAHL will be searched to identify published studies. Based on timing of the introduction of the United Nations on the Rights of Persons with Disabilities, searches will be conducted from 2006 onwards. There will be no language restrictions. Eligible studies will include primary cancer-related research that focuses on adults with intellectual and/or developmental disabilities and/or those involved in their care, including qualitative, quantitative, and mixed methods research. Two independent reviewers will screen titles, abstracts, conduct full text reviews, and extract information on how participants were recruited in research, and/or identified in administrative quantitative studies, and how they were involved. Information will also be extracted on how adults with intellectual and/or developmental disabilities were involved in the study based on the International Association for Public Participation spectrum (inform, consult, involve, collaborate, and empower). Our findings will help us better understand how adults with intellectual and/or developmental disabilities are engaged in cancer research and identify potential next steps for enhancing accessibility and inclusion in cancer research.